Intervalo de tempo de máxima previsibilidade no acoplamento de modelos climáticos e hidrológico para gerenciamento de reservatório - Cabral, Samuellson Lopes (2014)
This work seeks to integrate climatic, hydrologic, and reservoir operation models in order to optimize available water volume in the Brazilian Northeast. The global ECHAM 4.5 climate model was used to feed the RAMS regional climate model for the Alto Jaguaribe hydrographic basin. Resulting precipitation values were calibrated by the probability density function (PDF) correction of simulated data compared with average daily precipitation data using the Thiessen method for the period 1979-2009. The Heidke Skill Score (HSS) was used to evaluate model performance in the Maximum Predictable Time Interval (ITEMP) of the atmospheric model. These PDF-corrected precipitation data, both observed and RAMS-simulated, were inserted in the hydrologic Soil Moisture Account (SMA) model from the Hydrologic Engineering Center – Hydrologic Modeling System (HEC-HMS) to determine modeled flows. These flows were then compared with median observed flows. To calibrate and validate the SMA, an iterative method was used to minimize percentage error of volume. The data returned by this cascade model was applied to assisting policy-makers determine water releases from the Orós reservoir. Three different scenarios were compared, the first based on observed flows, the second flows simulated by SMA with observed precipitation, and the third by flows simulated by SMA driven by the RAMS-PDF precipitation data. The RAMS model showed optimal efficiency in precipitation prediction on a 30 to 45 day interval, with HSS values of 0.56. The SMA model showed satisfactory performance with Nash-Sutcliffe values of 0.89 in the calibration phase and 0.67 in the validation phase, demonstrating its capacity to assist hydrological modeling in the semi-arid. This cascade model showed potential in accurately representing median inflows for the reservoir and as such can be used as a hydrologic tool, assisting reservoir operation decisions to meet the region’s demand. Keywords: Soil Moisture Account; hydrologic